THE EFFECT OF THE TEAMS GAMES TOURNAMENT (TGT) COOPERATIVE LEARNING MODEL ON EIGHTH-GRADE STUDENTS' COGNITIVE SKILLS AND SCIENCE LEARNING MOTIVATION - Ela Sefitri; Rahmah Evita Putri; Khairil Arif; Azza Nuzullah Putri; Rani Oktavia (Department of Science Education, 2026)
Students' cognitive achievement and learning motivation are essential factors influencing success in science education. However, conventional teacher-centered instruction often provides limited opportunities for active participation, resulting in low cognitive learning outcomes and learning motivation. The Teams Games Tournament (TGT) cooperative learning model is designed to promote active engagement, collaboration, and healthy competition among students. This study aimed to examine the effect of the TGT cooperative learning model on eighth-grade students' cognitive learning outcomes and science learning motivation. A quasi experimental research design employing a posttest-only control group design was used. Participants were selected through purposive sampling, with one class assigned as the experimental group receiving instruction through the TGT cooperative learning model and another class serving as the control group receiving conventional instruction. Data were collected using a cognitive achievement test and a science learning motivation questionnaire. The data were analyzed using an independent-samples t-test for cognitive learning outcomes and descriptive statistics for learning motivation. The results showed that the experimental group obtained a higher mean cognitive score (60.0) than the control group (51.2). Furthermore, the independent-samples t-test indicated a statistically significant difference between the two groups (p < 0.05). The results also demonstrated an increase in students' science learning motivation following the implementation of the TGT cooperative learning model. These findings indicate that the TGT cooperative learning model has a significant positive effect on students' cognitive learning outcomes and science learning motivation.